Concurrent and aerobic exercise training promote similar benefits in body composition and metabolic profiles in obese adolescents - Monteiro, Paula Alves [UNESP] (2015)
Background: The prevalence of obesity in pediatric population is increasing at an accelerated rate in many countries, and has become a major public health concern. Physical activity, particularly exercise training, remains to be a cornerstone of pediatric obesity interventions. The purpose of our current randomized intervention trial was to compare the effects of two types of training matched for training volume, aerobic and concurrent, on body composition and metabolic profile in obese adolescents. Thus the aim of the study was compare the effects of two types of training matched for training volume, aerobic and concurrent, on body composition and metabolic profile in obese adolescents. Methods: 32 obese adolescents participated in two randomized training groups, concurrent or aerobic, for 20 weeks (50 mins x 3 per week, supervised), and were compared to a 16-subject control group. We measured the percentage body fat (%BF, primary outcome), fat-free mass, percentage of android fat by dual energy x-ray absorptiometry, and others metabolic profiles at baseline and after interventions, and compared them between groups using the Intent-to-treat design. Results: In 20 weeks, both exercise training groups significantly reduced %BF by 2.9-3.6 % as compare to no change in the control group (p = 0.042). There were also positive changes in lipid levels in exercise groups. No noticeable changes were found between aerobic and concurrent training groups. Conclusions: The benefits of exercise in reducing body fat and metabolic risk profiles can be achieved by performing either type of training in obese adolescents. Trial registration: Registration number: RBR-4HN597.